Differentiated Thyroid Cancer in Children: A UK Multicentre Review and Review of the Literature. Issue 6 (June 2019) - Lee, K.A.; Sharabiani, M.T.A.; Tumino, D.; Wadsley, J.; Gill, V.; Gerrard, G.; Sindhu, R.; Gaze, M.N.; Moss, L.; Newbold, K.
Abstract: Aims: To obtain an overview of the management and outcomes of children aged 18 years or younger diagnosed with differentiated thyroid carcinoma of follicular cell origin across the UK, by collecting and analysing data from the limited number of centres treating these patients. This multicentre data might provide a more realistic perspective than single-institution series. Materials and methods: Six centres submitted data extracted from historical records on patients aged 18 years or younger, diagnosed between 1964 and 2017. The univariate and multivariable Cox proportional hazard model was used to identify potential predictors of progression-free survival, using national data as a control. Results: Data on 166 patients were available for analysis. Females (74%) were predominant, and the age ranged from 3 to 19 years at diagnosis, mean 14.1 years. Nodal metastases were present in 51%; 12% had distant metastases. After surgery, 95% received radioactive iodine (39% on more than one occasion) and 4% received external beam radiotherapy. With a median follow-up duration of 5 years, 69% are alive with no evidence of disease; 20% are alive with a raised thyroglobulin level as the only evidence of residual disease; 6% have residual structural disease detectable on imaging; 2% have died, from cerebral metastases. Conclusion: Despite most patients having advanced disease at presentation, outcomes are very good. A national prospective registry should allow systematic collection of good-quality data and may facilitate research to further improve outcomes. Highlights: Paediatric thyroid cancer patients are treated in a small number of UK centres. Despite presentation with advanced disease, good long-term outcomes are expected. National prospective data collection is recommended.